Thymustumoren: eine klinische Betrachtung - Grosch, Heidrun; Weis, Cleo-Aron Thias; Hoffmann, Hans; Thomas, Michael (Der Pathologe, 2016)
Introduction: Thymic tumors including thymomas, thymic carcinomas, and thymic carcinoid tumors are rare tumors with an incidence of 0.13/100,000. Materials and methods: A literature search was performed to identify recent findings on epidemiology, classification, and various therapeutic approaches. Results: These tumors with a wide spectrum of histologic and biologic features may be clinically unapparent for a long time or show a very aggressive behavior with local invasion and distant metastases. Surgical resection is the mainstay in stage I and II thymomas, whereas in stage III thymomas and in thymomas with pleural dissemination surgery in context of a multimodal treatment should be discussed. Thymic tumors are chemoreactive. Targeted therapies show poor results and should only be considered in the palliative situation after failure of chemotherapy. Conclusion: The new TNM (T: tumor, N: node, M: metastasis) classification of thymic tumors will help to identify the best treatment options.